Proactive management of the economic and environmental impacts of a proposed oil sands mine in Nigeria from the pre-mining phase. - Omotehinse, Adeyinka Oluwayomi (2020)
The mining industry may have adverse impacts on the environment, ecosystems, ecosystem services and the society, all of which are essential to human well-being. The industry has understood that obtaining a formal license to operate from governments, meeting regulatory requirements is no longer enough, and in order to reduce risks for the stakeholders, a social license to operate needs to be obtained. Although impact of mining activities is experienced throughout the life of mine, pre-mining phase was considered in this research because it determines the relationship of the mining industries with the community. Despite the vast abundance of oil sands resources in Nigeria, an economic analysis is yet to be carried out to evaluate the feasibility of a mining operation at different production scales. Most importantly, this resource is associated with natural contamination referred to as bituminous natural effects. Therefore, mining is not only perceived to be an opportunity for both social-economic improvement by the local communities but also as an efficient approach to reduce exposure to bitumen fumes. To address these issues, this research aimed to carry out a pro-active study on some oil sands deposit communities in Nigeria. The methodology used include appraisal of questionnaire to the communities involved, applying an existing methodology of ecosystem services to the oil sands deposits located in Ondo State, Nigeria, modelling of the oil sands resource considering three mining scenarios taking into account synthetic crude oil, bitumen and tar production. A preliminary economic assessment and a sensitivity analysis was also carried out for three different production scales. The results of the research include an evaluation of the social license to operate locally; assessment of the impacts of pre-mining activities on the ecosystem services; and a preliminary economic assessment of three types of oil sands mining operations. The conclusions indicate that the challenges faced by a mining company can be managed if proper measures are taken and if the mining company communicates transparently with the community; in addition mining is perceived as a practical solution to the bituminous natural effects. Also, the ecosystem service assessment was proven to be an appropriate approach for mitigating impacts of pre-mining activities on ecosystem services. There will be opportunities for a public policy with minimum price guarantee so that small-scale mining of oil sands will be able to operate profitably and will help to solve the regional problem of untarred/unpaved roads. This will bring both economic and environmental benefits to both the local communities and the Nigerian government and it can represent an important driver for transformation to sustainability in the region.